2012
DOI: 10.1152/ajpgi.00033.2012
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the intrinsic inflammatory pathway: honokiol exerts proapoptotic effects through STAT3 inhibition in transformed Barrett's cells

Abstract: RF. Targeting the intrinsic inflammatory pathway: honokiol exerts proapoptotic effects through STAT3 inhibition in transformed Barrett's cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…Although EGCG (Nam et al , 2001) and HNK (Yu et al , 2012) may have other biological properties, studies showing that the AB 5 subtilase toxin, which cleaves GRP78 specifically, synergistically enhances the activity of ER stress inducers on melanoma cells (Martin et al , 2010) support the idea that chemical inhibitors of GRP78 may be effective as chemotherapeutic drugs. Nevertheless, although EGCG induces cell death and can overcome resistance to chemotherapeutic drugs (Ermakova et al , 2006; Virrey et al , 2008), on the basis of the present studies it did not have useful properties in combination with agents that induce ER stress.…”
Section: Discussionmentioning
confidence: 99%
“…Although EGCG (Nam et al , 2001) and HNK (Yu et al , 2012) may have other biological properties, studies showing that the AB 5 subtilase toxin, which cleaves GRP78 specifically, synergistically enhances the activity of ER stress inducers on melanoma cells (Martin et al , 2010) support the idea that chemical inhibitors of GRP78 may be effective as chemotherapeutic drugs. Nevertheless, although EGCG induces cell death and can overcome resistance to chemotherapeutic drugs (Ermakova et al , 2006; Virrey et al , 2008), on the basis of the present studies it did not have useful properties in combination with agents that induce ER stress.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown to increase necrosis and apoptosis in transformed but not in nontransformed Barrett's cells and exhibit a similar effect on adenocarcinoma cells [134]. There is a great deal of preliminary work required on the effect of STAT3 inhibition in BE and EAC; however, it remains a potential future therapeutic target.…”
Section: Dietary Chemopreventionmentioning
confidence: 99%
“…Honokiol may be used as an important therapeutic molecule to inhibit tumor angiogenesis and promote apoptosis [21, 26, 35]. Our present study for the first time shows that honokiol can promote apoptosis of renal cancer cells through the regulation of HO-1.…”
Section: Discussionmentioning
confidence: 53%
“…Thus, using inhibitors of these pathways in combination with CsA can be an ideal approach to attenuate the pro-tumorigenic effects of CsA without compromising its essential immunosuppressive functions. It has recently been suggested that honokiol, which has a great potential to inhibit tumor growth, may also down-regulate the Ras pathway [21, 26, 35]. A combination treatment with CsA and honokiol may be considered as a therapeutic strategy for preventing the development of post-transplantation renal cancer.…”
Section: Discussionmentioning
confidence: 99%